Intrinsic viscoelasticity of C-S-H assessed from basic creep of cement pastes. (July 2019) - Hu, Zhangli; Hilaire, Adrien; Ston, Julien; Wyrzykowski, Mateusz; Lura, Pietro; Scrivener, Karen
Abstract: This paper investigates the fundamental mechanisms behind the effect of supplementary cementitious materials (SCMs) on the basic creep behavior of cement pastes. The intrinsic creep properties of the C-S-H gel are assessed based on measurements of uniaxial compressive basic creep of cement pastes with different water-to-cement ratio (w/c), prepared either with pure cement or cement blended with fly ash or quartz. The viscoelastic response of the C-S-H was back-calculated from the macroscopic experimental creep results with Finite Element Method (FEM) homogenization. The numerical simulations show that the intrinsic viscoelastic behavior of the C-S-H gel follows a similar trend in different systems, independent of their w/c (in the range 0.35–0.63) and the binder used. The differences in the magnitude of the creep at the macroscopic scale in different cement-based systems appear to depend mainly on the volumetric fractions of the solid phases and on the porosity of the cement pastes.